A definitive guide to Apache ShardingSphere : build a new ecosystem above multi-model databases with a completely distributed database solution /: build a new ecosystem above multi-model databases with a completely distributed database solution. (2022) - Pan, Juan; Liang, Zhang; Tayeb, Yacine Si
No abstract available